2016
DOI: 10.1186/s40816-016-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological investigations of methanolic extract of Pouzolzia Zeylanica (L.) Benn

Abstract: Background: Phytochemical derived from plant consisting of phenols and flavonoids possess antioxidant properties, which are useful to scavenge reactive oxygen species (ROS). The aim of the work is to ascertain the level of antioxidant, cytotoxic, anti-microbial properties and in vivo analgesic and anti-inflammatory activity of methanolic extracts of Pouzolzia zeylanica (L.) Benn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…A group of secondary metabolite compounds has effective antimicrobial properties [36]. Mainly, methanol extract contains more antioxidant as because of this it might be used as folk medicide [37]. It was also reported that the methanol extract of B. monnieri exhibited the more significant inhibitory effect against Klebsiella pneumoniae, Staphylococcus aureus which corroborates with our findings [38,39].…”
Section: Discussionsupporting
confidence: 82%
“…A group of secondary metabolite compounds has effective antimicrobial properties [36]. Mainly, methanol extract contains more antioxidant as because of this it might be used as folk medicide [37]. It was also reported that the methanol extract of B. monnieri exhibited the more significant inhibitory effect against Klebsiella pneumoniae, Staphylococcus aureus which corroborates with our findings [38,39].…”
Section: Discussionsupporting
confidence: 82%
“…In both timeand dose-dependent treatment protocols it was monitored that long-term (12 weeks) treatment showed a drop of glucose level compared to short-term (8 weeks) treatment. In both cases only combination therapy showed significance and was supported by preceding studies [46,47,[94][95][96][97][98][99][100][101].…”
Section: Discussionsupporting
confidence: 77%
“…More than sixty plants used for green AgNP synthesis were summarized [11,14], but Phyllanthus urinaria (P. urinaria), Pouzolzia zeylanica (P. zeylanica), and Scoparia dulcis (S. dulcis) are plants of interest that have not yet been explored. P. urinaria, P. zeylanica, and S. dulcis are traditional herbs distributed mainly in tropical countries [22][23][24][25][26][27]. In folk medicine, P. urinaria is well known as a remedy for treating many diseases, including diabetes, jaundice, malaria, cancer, infection, and liver diseases [24][25][26].…”
Section: Introductionmentioning
confidence: 99%